Connecting Sequence and Biology in the Laboratory Mouse - Baldarelli, Richard M.; Hill, David P.; Blake, Judith A.; Adachi, Jun; Furuno, Masaaki; Bradt, Dirck; Corbani, Lori E.; Cousins, Sharon; Frazer, Kenneth S.; Qi, Dong; Yang, Longlong; Ramachandran, Sridhar; et al.

(untitled) (Genome Research, 2003)
The Mouse Genome Sequencing Consortium and the RIKEN Genome Exploration Research grouphave generated large sets of sequence data representing the mouse genome and transcriptome, respectively. These data provide a valuable foundation for genomic research. The challenges for the informatics community are how to integrate these data with the ever-expanding knowledge about the roles of genes and gene products in biological processes, and how to provide useful views to the scientific community. Public resources, such as the National Center for Biotechnology Information (NCBI; http://www.ncbi.nih.gov), and model organism databases, such as the Mouse Genome Informatics database (MGI; http://www.informatics.jax.org), maintain the primary data and provide connections between sequence and biology. In this paper, we describe how the partnership of MGI and NCBI LocusLink contributes to the integration of sequence and biology, especially in the context of the large-scale genome and transcriptome data now available for the laboratory mouse. In particular, we describe the methods and results of integration of 60,770 FANTOM2 mouse cDNAs with gene records in the databases of MGI and LocusLink.